A study of the relationship between "fatigability of acoustic reflex" and temporary threshold shift - Kamakshi (Journal of All India Institute of Speech and Hearing)
It has been generally recognized that there are individual differences in the susc ptibilityof ears to damage from noise. Many references have been made in the literature to ’tough ears’ and ’tender ears’ referring to differences in degree of susceptibility.